Improving EFL Reading Comprehension through Self-Regulated Learning Strategies: An Intervention Study at SMK PGRI 2 Kediri - Maulidiyah, Miftah Dwi Putri; Khoiriyah, Khoiriyah; Sulistyani, Sulistyani (Proceeding International Conference on Education, 2025)
This study investigates the influence of Self-Regulated Learning (SRL) strategies on the reading comprehension of English as a Foreign Language (EFL) students at SMK PGRI 2 Kediri. Students' reading comprehension is often suboptimal, exacerbated by the lack of utilization of SRL. Based on Zimmerman's SRL theory (planning, monitoring, self-evaluation) and Brown's (2004) indicators of reading comprehension, this study aims to test the hypothesis of a significant influence of SRL. Using a quantitative One-Group Pretest-Posttest design, 29 students from class X AK 2 were selected through purposive sampling. The SRL intervention was conducted in two sessions, focusing on training in planning, monitoring, and self-evaluation in reading. Data were collected through pre-test and post-test measures assessing the ability to identify main ideas, vocabulary in context, details, and inferences. Descriptive results showed an increase in the average reading comprehension score from 66.41 (pre-test) to 82.29 (post-test), with the passing rate increasing from 37.93% to 71.4%. The Shapiro-Wilk normality test indicated that the data were not normally distributed (p<0.05). Therefore, hypothesis testing used the Wilcoxon Signed-Rank Test, which showed a significance value of 0.000 (p<0.05). These results confirmed the rejection of the null hypothesis, proving the positive and significant effect of the SRL strategy on students' reading comprehension. The discussion shows that each phase of SRL contributes to the improvement of specific reading comprehension indicators. This study reinforces the literature supporting the effectiveness of SRL in the context of foreign language learning and provides practical implications for teaching English in senior high school level.